Passion fruit juice concentration using fabricated cellulose triacetate/cellulose acetate forward osmosis membrane - Mohamad Idris, A.I.; Mustapa Kamal, S.M.; Sulaiman, A.; Omar, R.; Mohammad, M. (Rynnye Lyan Resources, 2024)
The concentration of juice using an evaporator is an energy-intensive process. Forward osmosis membrane can be used as an alternative for juice concentration at significantly low energy. In this work, fabricated cellulose triacetate (CTA)/cellulose acetate (CA) forward osmosis membrane was applied to concentrate passion fruit juice. The feasibility of the fabricated CTA/CA membrane on concentrating the passion fruit juice was determined. The FO membrane was prepared by fabricating the mixture of CTA/CA with the inclusion of polyvinylpyrrolidone (PVP) as an additive. The CTA/CA forward osmosis membrane was characterized and compared with the fabricated pure CA membrane (with the inclusion of PVP). The synthesized CTA/CA membrane was shown to have a high porosity, desired hydrophilicity, and a reduced impact of ICP, which generally affected the forward osmosis process. The concentration of passion fruit juice was successfully performed at an average of 2.2 LMH of water flux. The latter showed that the fabricated CTA/CA forward osmosis membrane has the potential to concentrate the passion fruit juice. It can be further improved by increasing the concentration of the draw solution (NaCl) or using another type of draw solution that has higher osmotic pressure.